Implementation of Literacy Management in SMK Negeri 3 Singkawang - Gunanto Gunanto (STKIP Singkawang, 2019)
Efforts to make schools as learning organizations whose citizens have lifelong literature by utilizing their resources. The main supporter of the School Literacy Movement (GLS) has been owned, namely the SMK Negeri 3 Singkawang library that provides a variety of quality reading books, but in real interest in reading and intensity of borrowing books by students is still minimal. The information obtained is the existence of various things that are considered as obstacles, including (1) the availability of quality books in the neighbourhood, (2) the distance between classes to the library room that is not close, (3) the complexity of the procedure for borrowing books in the library, (4) the time limit for borrowing at the library, (5) there is reluctance towards library staff. The purpose of this study is (1) to describe literacy planning in SMK Negeri 3 Singkawang, (2) describe the implementation of literacy activities in SMK Negeri 3 Singkawang, (3) describe the literacy supervision activities in SMK Negeri 3 Singkawang. The Research Method used descriptive qualitative research. The study was conducted in SMK Negeri 3 Singkawang. The research subjects were students of class X in the academic year 2017/2018, data collection techniques used were interviews, observation and documentation study. As well as triangulation of sources and techniques to ensure the validity of the data. Evaluation results Implementation of the reading corner policy beginning in June 2018 in class X students in the academic year 2017/2018 was that all students (100%) have borrowed library books, all students (100%) have read books non-subjects, 100% of students have made a resume of the contents of at least 1 non-text reading book that they read, 69.6% of students felt that the presentation of the results of resume books can improve the ability to speak in front of the crowd. This study concluded that (1) The planning of the liberation movement in SMK Negeri 3 Singkawang was realized by the formation of the GLS team, Cadre Officers and library classes/reading corners. (2) The implementation of literacy activities in SMK Negeri 3 Singkawang has shown progress shown by the enthusiasm of students to read to increase. (3) The supervision of the literacy movement in SMK Negeri 3 Singkawang is jointly conducted between the GLS team and Indonesian language teachers.